PENGARUH KOMUNIKASI EFEKTIF TERHADAP KINERJA PETUGAS ADMINISTRASI PENDAFTARAN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Febby Dwi Kinanti; Wiwik Suryandartiwi, Agus Salim, Anastasya Shinta Yuliana (CV. Adiba Aisha Amira, 2024)
Effective communication is a process in communication that can produce attitude change. The purpose of this study was to determine the effect of effective communication on the performance of outpatient registration administrative officers at the regional general hospital arifin achmad riau province. This study uses a type of quantitative research using a cross sectional design, conducted at the regional general hospital arifin achmad riau province with a total of 100 respondents, namely outpatient registration patients. This research was carried out by conducting several stages of analysis, including assumption analysis, multiple regression analysis, coefficient of determination, T test and F test. The results of this study state that the sig. value is 0.000 which shows that 0.000 <0.05, so the conclusion is that there is a significant influence between effective communication (personal factors, environmental factors, relationship factors) on the performance of outpatient registration administrative officers at Arifin Achmad Regional General Hospital.The conclusion of this study is that there is an effect of effective communication on the performance of outpatient registration administrative officers at the Arifin Achmad Regional General Hospital, Riau Province. Suggestions for the 5S culture banner (smile, greeting, greeting, courtesy, and courtesy) in the outpatient registration room. It is hoped that officers can carry out the 5S culture, so that there is effective communication between fellow officers and officers and patients who register.